2015
DOI: 10.1620/tjem.237.339
|View full text |Cite
|
Sign up to set email alerts
|

Eldecalcitol, in Combination with Bisphosphonate, Is Effective for Treatment of Japanese Osteoporotic Patients

Abstract: Alfacalcidol (ALF) and eldecalcitol (ELD) are vitamin D analogues that can be combined with anti-resorption drugs, such as bisphosphonate (BP) for the treatment of osteoporosis (OP). There has been no report comparing the effects of those vitamin D analogs in combination with BPs. Twenty female patients with OP were enrolled, and all of them were treated with ALF and BPs. After switching from ALF to ELD, we examined the effectiveness of ALF and ELD. The averaged age was 69.4 years and the period of BP usage wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…In this study, a 0.9% increase of FN-BMD with ELD at six months in Case 1 and a 2.4% gain in FN-BMD without ELD at four months in Case 2 were observed during denosumab therapy. Nonetheless, a combination therapy of anti-resorption drugs and vitamin D, such as ELD, may produce better effects on bone metabolism and BMD, as reported previously [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In this study, a 0.9% increase of FN-BMD with ELD at six months in Case 1 and a 2.4% gain in FN-BMD without ELD at four months in Case 2 were observed during denosumab therapy. Nonetheless, a combination therapy of anti-resorption drugs and vitamin D, such as ELD, may produce better effects on bone metabolism and BMD, as reported previously [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 59%
“…Vitamin D is required for optimal BMD increase during denosumab treatment [ 16 ]. ELD, an analog of active vitamin D3, could improve BMD and reduce the risk of osteoporotic fractures [ 17 ]. We previously reported that a combination therapy with denosumab and ELD ameliorated FN-BMD more effectively than did denosumab plus native vitamin D [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The drug therapy with bisphosphonate is recommended and safe for beneficial effects on bone health in postmenopausal women, especially, when there is an increased risk of fracture in hip and lumbar spine (Diab & Watts, 2013;Reginster, 2011). According to a study of Mukaiyama et al (2015) the combined effect of alendronate with alfacalcidol and eldecalcitol (analogous to vitamin D), showed significant improvement in BMD of the lumbar spine, maintenance the femur neck and showed no improvement in hip BMD after one year of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the GC not was observed increase BMD (p < 0.05) in the variables, characterized as a BMD maintenance. Although the drug was not analyzed as an independent variable, it was likely that the drug can have contributed to the increase or maintenance of the BMD, because, there is evidence that a combination of PA with alendronate shows positive effects on BMD (Mukaiyama et al, 2015;Uusi-Rasi et al, 2003). Therefore, together, alendronate and PA can be more efficient in reducing the risk of fracture (Borba-Pinheiro et al, 2010;Uusi-Rasi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy of a BP and ALF is frequently used for Japanese patients with OP since ALF has been approved as an osteoporotic drug. However, there are few reports on combined therapy using a BP and ALF, and the precise effects of ALF on BP treatment for OP is controversial (Iwamoto et al 2003;Ringe et al 2007;Orimo et al 2011;Mukaiyama et al 2015). Furthermore, little is known on the role of ALF during IBN treatment in patients with OP.…”
Section: Introductionmentioning
confidence: 99%